Muscle madness and making a case for muscle-specific classification systems: A leap from tissue injury to organ injury and system dysfunction - Balius, R.; Pedret, C.; Kassarjian, A. (Sports Medicine, 2021)
Despite the recent publication and subsequent clinical application of several muscle injury classification systems, none has been able to address the varying and often unique/complex types of injuries that occur in different muscles. Although there are advantages of using a unified classification, there are significant differences between certain muscles and muscle groups. These differences may complicate the clinical effectiveness of using a unified injury classification. This narrative explores the difficulties in using a single classification to describe the heterogeneous nature of muscle injuries. Within that context, the possibility of viewing muscles and muscle injuries in the same manner as other biological tissues, structures, organs, and systems is discussed. Perhaps, in addition to a unified classification, subclassifications or muscle specific classifications should be considered for certain muscles. Having a more specific (granular) approach to some of the more commonly injured muscles may prove beneficial for more accurately and effectively diagnosing and treating muscle injuries. Ideally, this will also lead to more accurate determination of the prognosis of specific muscle injuries.